ZOOM OUT GEOGRAPHIC LOCATION SERVICE (ZGLS): A FLAT QUORUM-BASED AND RELIABLE LOCATION MANAGEMENT PROTOCOL FOR VANETs - ,, MUHAMMAD MAAZ REHAN (2015)
By using position-based routing in Y ANET, a vehicle makes forwarding decision based on the geographic position of destination and single-hop neighbours. The position of a destination is obtained through location service, while the positions of single-hop neighbours are obtained through neighbour discovery. Location service is a process where a destination sends its location updates towards location server vehicles through hop-by-hop t(mvarding, and a source obtains this information tram such location servers through location query. Neighbour discovery is a process where a vehicle advertises its position to all neighbours within a broadcast range. In many cases, adaptive neighbour discovery schemes are more suitable, but they suffer from high channel load and stale neighbour information. For location service, floodingbased model suffers from congestion. throughput and scalability problems due to global flooding; flat hashing-based model uses global hash function and suffers from network scalability due to delay, drop and overhead of location updates and queries; hierarchical hashing-based model also uses a global hash function and suffers from handover signalling, uneven load on higher level servers and query delay; hierarchical quorum-based model.